2021
DOI: 10.1007/s10734-021-00755-y
|View full text |Cite
|
Sign up to set email alerts
|

Reconceptualising fair access to highly academically selective universities

Abstract: The higher education regulator for England has set challenging new widening access targets requiring universities to rethink how merit is judged in admissions. Universities are being encouraged to move away from the traditional meritocratic equality of opportunity model of fair access, which holds that university places should go to the most highly qualified candidates irrespective of social background, in accordance with the principles of procedural fairness. Instead, they are being asked to move towards what… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Indeed, the case-study approach adopted here is intensive rather than exhaustive. That said, and whilst the results are necessarily descriptive of the sample-and the quantitative component is, perhaps, not as recent as we might wish-moderate generalizations can be made and there is reason to suspect that many of the findings would resonate and transfer across faculties and other similar universities [1,21,36]. We also recognize that issues relating to class and socio-economic circumstance are likely to feature heavily in the experiences of some BME groups.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Indeed, the case-study approach adopted here is intensive rather than exhaustive. That said, and whilst the results are necessarily descriptive of the sample-and the quantitative component is, perhaps, not as recent as we might wish-moderate generalizations can be made and there is reason to suspect that many of the findings would resonate and transfer across faculties and other similar universities [1,21,36]. We also recognize that issues relating to class and socio-economic circumstance are likely to feature heavily in the experiences of some BME groups.…”
Section: Discussionmentioning
confidence: 85%
“…They are widely perceived to have a research-intensive focus and are selective, attracting some of the highest achieving students in the country. However, while recent research has demonstrated that applicants from traditionally underrepresented groups are less likely to be offered places than their peers [4,5,36], there has been comparatively little exploration of how this might be translated into the experiences of BME students who do enter such institutions.…”
Section: Contextmentioning
confidence: 99%
“…Worryingly, these disparities persist even after controlling for attainment at Key Stages 4 and 5. It should be noted, however, that the cohort to which these findings relate came of traditional university‐going age in 2008, 10 years prior to the replacement of the Office for Fair Access by the Office for Students and the subsequent introduction of new widened access targets for England's most selective universities (Boliver et al., 2022). Given that the most selective universities have since committed to achieving these new targets and implementing a range of measures to better support socioeconomically disadvantaged students into and through university (Boliver & Powell, 2023), it is to be hoped that disparities in university entry rates are less pronounced for contemporary 18 year olds.…”
Section: Discussionmentioning
confidence: 99%
“…Universities tend to be conceived and designed for traditional students, who are not emancipated and for whom studying is their main activity. The rigidity of Spanish university structures hinders the university careers of other students, increasing educational inequality by favouring those who have sufficient means, generally provided by families, to be able to dedicate themselves exclusively to studies [51]. This is of special relevance for the Roma community because it is a group with significant economic needs and they rarely receive from their families the necessary economic support to dedicate their time exclusively to university.…”
Section: Discussionmentioning
confidence: 99%